LEVEL OF LANDSLIDE SUSCEPTIBILITY IN CIBAL DISTRICT OF MANGGARAI EAST NUSA TENGGARA - Dominikus Victorius Bate; Puguh Karyanto; Moh. Gamal Rindarjono (Department of Geography Education, University of Jember, 2018)
This research aims to determine the degree of susceptibility of landslides in Cibal Districts. The method used in this research is descriptive survey method. The population in this research is all of the land in Cibal Districts. data collection technique is done by using observation technique and documentation study. Data analysis technique in this research uses crosstab technique. The results of this study can be seen that the level of susceptibility of landslides in Cibal based on crosstab results, there are three categories of vulnerability of landslide , they are low, medium and high. Low landslide susceptibility rate of 6.979,65 hectares or 64.09% is found in Nine sub-districts / village. The moderate landslide susceptibility rate has an area of 3,634.67 hectares or 33.38%, in seven villages. While the high landslide susceptibility rate is found only in one village with an area of 275.65 hectares or 2.35% of the total area of Cibal districts. Keywords: Susceptibility, Landslide, Cibal District References Aditya, Triyas & Marjuki, Bramantyo, (2009) Preparation of DIY Province Risk Map. Yogyakarta: Provincial Government of DIY & PPMU SCDRRRegional Disaster Mitigation Agency (BPBD) of Manggarai Regency in 2017 Nurjanah. 2012. Disaster Management. Bandung: Alfabeta Regulation of National Agency for Disaster Management 04 of 2008 on guidelines for the preparation of disaster management Ministry of Public Works Regulation No. 22 of 2007 Muta'ali. 2012. Environmental Support Capacity for Regional Development Planning. Yogyakarta: Faculty of Geography Gadjah Mada Univercity. Gems, S. 2016. Risk Management And Landslide Mitigation. UGM: YogyakartaSugiyono. 2016. Quantitative Research Methods, Qualitative, And R & D. Bandung: AlfabetaSupretno, J. (1996). Statistics, Theory and Applications. Jakarta: Erlangga Suripin.2002. Preservation of Land and Water Resources.Yogyakarta. Copyright (c) 2018 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License